1999
DOI: 10.1088/0268-1242/14/2/006
|View full text |Cite
|
Sign up to set email alerts
|

Atomic model for blue luminescences in Mg-doped GaN

Abstract: We investigate the origin of the broad luminescence observed around 2.7-2.9 eV in heavily Mg-doped GaN through first-principles pseudopotential calculations. We find that a defect complex composed of an Mg interstitial (Mg i ) and an N vacancy (V N ) gives rise to optical transition levels around 2.8 eV above the valence band maximum, suggesting that the blue luminescences are caused by deep-donor-to-valence-band transitions. The formation of the Mg i -V N complex is enhanced by hydrogenation and is more prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…From 150 K to 50 K, the PL intensity of the UV band was dominantly increased over two orders of magnitude and also the intensity of the blue band shows some increase due to the long lifetime of DAP transition and short lifetime of e-A transition. The change in PL intensity at 150 K can be explained by transition from the blue to UV band due to thermal quenching of electrons [3 -5] and Mg i -V N [6]. The Fermi energy in p-GaN used here is located far from the valence band due to low the hole concentration even though high Mg-doping was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…From 150 K to 50 K, the PL intensity of the UV band was dominantly increased over two orders of magnitude and also the intensity of the blue band shows some increase due to the long lifetime of DAP transition and short lifetime of e-A transition. The change in PL intensity at 150 K can be explained by transition from the blue to UV band due to thermal quenching of electrons [3 -5] and Mg i -V N [6]. The Fermi energy in p-GaN used here is located far from the valence band due to low the hole concentration even though high Mg-doping was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Kaufmann, et al, did some extensive studies [75,90], from which they concluded that the BL [28], although another theoretical group has proposed that the BL is caused by a DD-VB transition, with the deep donor being a defect complex composed of a Mg interstitial (Mg i ) and a nitrogen vacancy whose formation is enhanced by hydrogenation [92].…”
Section: Self-compensationmentioning
confidence: 99%
“…The possible way to obtain additional information about defects (including native defects) and their properties, such as energy level structure, spatial configuration, charge state etc., is the numerical calculation. Big amount of work has been performed using different variations of the first-principle calculations with periodic pseudopotential, both for ZnSe [1][2][3][4][5][6][7][8][9][10][11] and GaN [12][13][14][15][16][17][18][19][20] . These theoretical studies provide a lot of useful information, for example, of one related to the formation energy, energetic structure and charge density, but, being well suitable for calculation of energy parameters of centers, they may give inadequate results concerning their spatial structure.…”
Section: Introductionmentioning
confidence: 99%